2012
DOI: 10.1134/s0006297912080147
|View full text |Cite
|
Sign up to set email alerts
|

Impact on N-Glycosylation profile of monoclonal anti-D antibodies as a way to control their immunoregulatory and cytotoxic properties

Abstract: Prophylaxis of hemolytic disease of newborns is based on the ability of polyclonal anti-D antibodies for suppressing maternal immune response against D-positive fetal red blood cells. The immunosuppressive effect of anti-D antibody is mediated by interaction between its Fc-fragment and low-affinity IgG Fc-receptor (FcγR) on the immune cell. No clinically effective monoclonal anti-D antibody (mAb) that can replace polyclonal anti-D immunoglobulin has been developed yet. The goals of this study were comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Although not universally agreed upon, the most commonly accepted theories to explain the AMIS effect with erythrocytes are 1) that the AMIS Ab is able to rapidly clear Ag-positive target cells before they can be recognized by the immune system (10-12, 16, 17), theoretically based on FcgRmediated phagocytosis of D + RBCs preventing B cells from recognizing the D Ag (10,11,17), or 2) that the AMIS Ab sterically hinders the ability of the immune response to see or detect the Ag (4,15,16,18). Other theories with direct experimental support have suggested that inhibition may occur through the inhibitory FcgRIIB (19), that inhibitory cytokines may be produced (20), that glycosylation of the AMIS Ab may play a role (21)(22)(23), and/or that Abmediated immune deviation (AMID) away from the Ag and directed toward the sensitizing Ab may be involved (5). In addition to these theories, a number of others have been proposed (Table I).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although not universally agreed upon, the most commonly accepted theories to explain the AMIS effect with erythrocytes are 1) that the AMIS Ab is able to rapidly clear Ag-positive target cells before they can be recognized by the immune system (10-12, 16, 17), theoretically based on FcgRmediated phagocytosis of D + RBCs preventing B cells from recognizing the D Ag (10,11,17), or 2) that the AMIS Ab sterically hinders the ability of the immune response to see or detect the Ag (4,15,16,18). Other theories with direct experimental support have suggested that inhibition may occur through the inhibitory FcgRIIB (19), that inhibitory cytokines may be produced (20), that glycosylation of the AMIS Ab may play a role (21)(22)(23), and/or that Abmediated immune deviation (AMID) away from the Ag and directed toward the sensitizing Ab may be involved (5). In addition to these theories, a number of others have been proposed (Table I).…”
mentioning
confidence: 99%
“…In fact, regulators consider that for the prevention of HDFN a mAb specific for the RhD Ag should be demonstrated to cause RBC clearance before exposing pregnant women to the product. Along the lines of enhancing red cell clearance to derive an optimized mAb, additional attempts to biochemically increase the ability of some RhD-specific mAbs to cause increased red cell clearance characteristics by manipulating the carbohydrate structure on the Fc portion of the molecule have been performed (21,22). Unfortunately, we do not as of yet have a monoclonal anti-D Ab that has proved successful for the prevention of HDFN, and some anti-D Abs with good red cell clearance abilities have actually led to an enhanced alloimmune response rather than inhibition (22,23).…”
mentioning
confidence: 99%
“…Afucosylated IgG has high affinity for FcγRIIIa 22,47 displacing plasma IgG and enabling ADCC at low concentrations 48 . Many alloantibodies, but not all, have considerably less fucose than total IgG1 [22][23][24][25]49 . Fucosylation of anti-D in 11 prophylactic preparations was 56%-91%, while for Rhophylac this was 81% 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Methods used for other studies reported in Supplementary Table S1 were MALDI-TOF-MS analysis of IgG1 Fc-glycopeptides 25 , analysis by HVE-AEC, gel filtration chromatography and Concanavalin A binding of oligosaccharides released by hydrazinolysis 109 , quantitation of % G0 by binding of GlcNAc-specific mAb GN7 59 , chromatographic separation of fluorescently labelled neutral oligosaccharides 49 , enzymatically released glycans analysed by HPCE-LIF 82 and FAB-MS and MALDI-MS of permethylated N-glycans (Carbohydrate structure of rBRAD-3 and rBRAD-5; Joan Dalton, BioProducts Laboratory, UK, email, September 26, 2007; permission to publish subsequently given).…”
Section: Analysis Of Mab-d Glycosylation In Small Scale Earlier Studiesmentioning
confidence: 99%
“…Anti‐D immunoglobulin is currently derived from human plasma of immunised, boosted donors. Monoclonal anti‐D is not available as a substitute and recombinant anti‐D was ineffective in several trials (Kumpel, ), although development and glycosylation research is ongoing (Olovnikova et al , ; Yver et al , ).…”
Section: Discussionmentioning
confidence: 99%